Correlates of Social Work Students' Abortion Knowledge and Attitudes: Implications for Education and Research. Issue 4 (6th June 2016) - Begun, Stephanie; Bird, Melissa; Ramseyer Winter, Virginia; Massey Combs, Katie; McKay, Kimberly
Abstract : Researchers have established that individuals' abortion knowledge is positively associated with their support of abortion rights. However, social workers' personal beliefs regarding abortion are under-researched, even though social workers are often employed in health promotion and education roles in which the topic of abortion is encountered. The current study examines the results of a nationwide survey of social work students (N = 504) and explores the relationship between social work students' abortion knowledge and abortion attitudes. Less abortion knowledge was significantly associated with antichoice attitude endorsement. Implications for social work research, training, and education are subsequently discussed.